Pengaruh Variasi Ukuran Ketebalan Material terhadap Karakteristik Termoelektrik Komposit CuO/Karbon Aktif Kulit Pisang Kepok - Aisyi, Rihadatul; Putra, Ananda (Darul Yasin Al Sys, 2023)
Thermoelectric is a device that can convert heat energy into electrical energy. One thing that influences the quality and characteristics of a thermoelectric material is the size of the thermoelectric material. In this research, we will look at the effect of the size of the thermoelectric material which has been varied in thickness. The thermoelectric material itself is made from a composite of active carbon from kepok banana peel with CuO with a mass ratio of 3:7. The composite was then printed with varying mold thickness sizes and the results were that a mold with a thickness of 0.5 cm was the best mold with an electrical conductivity value of 0.2 MS/cm, a heat conductivity value of 0.0680394 J/s, a value the Seebeck coefficient is 1.13229 mV/oK. The band gap value of the activated carbon and CuO composite resulting from the DR-UV test is 1.27 eV